Correction: Additive-mediated intercalation and surface modification of MXenes. (16th March 2022) - Zou, Jing; Wu, Jing; Wang, Yizhou; Deng, Fengxia; Jiang, Jizhou; Zhang, Yizhou; Liu, Song; Li, Neng; Zhang, Han; Yu, Jiaguo; Zhai, Tianyou; Alshareef, Husam N.
Abstract : Correction for 'Additive-mediated intercalation and surface modification of MXenes' by Jing Zou et al., Chem. Soc. Rev., 2022, DOI: ; 10.1039/d0cs01487g .